The assessment of the patients disability degree using the EDSS scale in various forms of multiple sclerosis - Magda Kucharczuk; Karolina Małgorzata Juraszek; Stanisław Krajewski; Marta Surman-Wika; Karol Tkaczyński (Kazimierz Wielki University, 2018)
Purpose. The aim of the study is to assess the patients disability degree using the Extended Scale of Disability in various forms of multiple sclerosis. Material and Methods. The study was conducted on a group of 40 people suffering from multiple sclerosis, diagnosed and treated in the Neurology Clinic of the 10th Military Clinical Hospital in Bydgoszcz. In order to assess the patients disability degree, the Extended Disability Management Scale was used. The other information needed for statistical analysis was obtained from the clinical observation chart established for each patient.Results. The disability degree of patients with multiple sclerosis is determined by many variables. The Expanded Disability Rating Scale is a good tool to assess the degree of disability of patients with multiple sclerosis.Conclusion. 1. In the group of people with relapsing remitting MS, the average value of the degree of disability in the Expanded Disability Scale was the smallest. 2. The childbirth during the course of multiple sclerosis causes exacerbation of clinical symptoms immediately after the childbirth. 3. Optic neuritis as the initial symptom of multiple sclerosis predisposes to a milder course of the disease. 4. Symptoms of the first relapse of multiple sclerosis that support faster progression of disability are: lower limb paresis, sphincter dysfunction and balance disorders. 5. Multifocal symptomatology of the first relapse of multiple sclerosis speaks for faster progression of disability in relation to patients with the first relapse characterized only by one symptom.